2017
DOI: 10.1103/physrevb.95.115201
|View full text |Cite
|
Sign up to set email alerts
|

Atypically small temperature-dependence of the direct band gap in the metastable semiconductor copper nitrideCu3N

Abstract: The temperature-dependence of the direct band gap and thermal expansion in the metastable anti-ReO 3 semiconductor Cu 3 N are investigated between 4.2 and 300 K by Fourier-transform infrared spectroscopy and x-ray diffraction. Complementary refractive index spectra are determined by spectroscopic ellipsometry at 300 K. A direct gap of 1.68 eV is associated with the absorption onset at 300 K, which strengthens continuously and reaches a magnitude of 3.5×10 5 cm −1 at 2.7 eV, suggesting potential for photovoltai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 78 publications
(102 reference statements)
5
18
0
Order By: Relevance
“…From Fig. 3(b), the peak in absorption coefficient at around 2.8 eV is consistent with that observed in the absorption coefficient spectrum measured using spectroscopic ellipsometry in [35]. Although only direct transitions are considered in this calculation, non-zero values of ε 2 (ω) are observed between 0 eV and 1.8 eV, due to the fact that density functional theory calculations are only theoretical approximations to actual materials.…”
Section: Results From First-principles Calculationssupporting
confidence: 82%
See 2 more Smart Citations
“…From Fig. 3(b), the peak in absorption coefficient at around 2.8 eV is consistent with that observed in the absorption coefficient spectrum measured using spectroscopic ellipsometry in [35]. Although only direct transitions are considered in this calculation, non-zero values of ε 2 (ω) are observed between 0 eV and 1.8 eV, due to the fact that density functional theory calculations are only theoretical approximations to actual materials.…”
Section: Results From First-principles Calculationssupporting
confidence: 82%
“…While the measured absorption coefficient spectrum for Cu 3 N in Fig. 8 is in overall agreement with that reported in [3,17,35], we emphasize that optical absorption below the direct bandgap of 1.82 eV is mediated by Cu i defects and will not be present in the pristine defect-free Cu 3 N crystal.…”
Section: A Optical Absorption In Cu 3 Nsupporting
confidence: 88%
See 1 more Smart Citation
“…70 Its crystal structure in space group P m3m is the same as that of 68 tetragonal structure, which is not surprising given the open nature of the structure. 71 There has not been a detailed study of NTE in Cu 3 N, but a recent report indicates that there is little, if any, expansion in the temperature range of 4 K -100 K. 72 More than fifty years from its discovery elapsed before the growth of thin films was reported, 73 and attention was drawn to the interesting semiconducting properties of Cu 3 N. Shortly afterwards, in 1990, it was shown that such films, which are typically green, could be used as an optical data recording medium using infrared light. 74 Since copper does not react directly with nitrogen gas, the films were made by irradiating copper with nitrogen ions during film deposition onto a substrate (though bulk samples can be made from the reaction between CuF 2 and NH 3 ).…”
Section: Inorganicsmentioning
confidence: 99%
“…Although the Cu 3 N film alone has better photocatalytic performance, it still has some shortcomings, so researchers often dope or recombine Cu 3 N with other materials. Cu 3 N has a ReO 3 structure, and the eight corners of the cubic crystal are occupied by N atoms; each side of the unit cell has a Cu atom, and many vacancies are present in the center of the unit cell [36][37][38][39]. These vacancies can be filled by other atoms (e.g., Pb [40], Ag [33], and Sc [41]), thereby changing the Cu 3 N band gap width and consequently its electrical and optical properties.…”
mentioning
confidence: 99%